Desenvolvimento de bandas de rodagem para pneus de automóvel com aditivos alternativos - Moresco, Suélen (My University, 2014)
The present study aimed at characterizing and determining the technical viability of a natural rubber tread (NR) with the incorporation of oil proceeding from vegetable source and vulcanization activator with less zinc content (organic Zn). These additives were used in replacement to the components traditionally used in the rubber industry, aiming at reducing the quantity of zinc in the formulation and application of oil proceeding from vegetable source as plasticizer/lubricant. The study has been begun with the chemical and thermal characterization of each alternative additive from the thermogravimetric analysis (TGA), infrared spectrometry with Fourier transform (FTIR) and atomic absorption spectrometry (AAS). The mixtures were prepared in a Banbury and the incorporation of the acceleration components was performed in an open mixer. Fifteen mixtures were prepared, being one standard and the other ones varying the content of vegetable oil (3, 4, 6 and 8 phr), organic Zn (2, 3, 4 and 5 phr) and both additives together (2 and 3 phr of organic Zn with 3 phr of vegetable oil). It was also prepared a standard formulation typical of tread and formulations with ZnO, being the Zn content equivalent to proposed formulations. The characterization of the compositions was performed through the rheometric properties, differential scanning calorimetry (DSC), crosslink density, rubber processing analyzer (RPA), dynamicmechanical thermal analysis (DMA), X-Ray diffraction, ageing accelerated in heater and the physical-mechanical properties of density, hardness, tensile strenght, tear strenght, abrasion loss and compression set. All the results have been compared to the standard formulation to treads. The thermal and chemical characteristics suggested that the oil proceeding from vegetable source presents a typical structure of soybean oil obtained through a transesterification reaction with phenol and the organic zinc presents typical structure of aromatic zinc carboxylate. The DSC analysis confirmed the lubricant effect of the oil proceeding from vegetable source, in as much as there hasn’t been temperature diminution in glass transition of the compounds. The physicalmechanical properties and the ageing accelerated in heater indicate that the best performance has been achieved with 3 phr of organic Zn and 3 phr of oil proceeding from vegetable source, causing a diminution of 50% of plasticizer oil content and 75% of zinc content, without affecting unfavorably the properties of the final artifact.
O objetivo dessa dissertação foi caracterizar e determinar a viabilidade técnica e desenvolvimento de uma banda de rodagem de borracha natural (NR) com a incorporação de óleo proveniente de fonte vegetal (OV) e ativador de vulcanização com menor teor de Zn (Zn orgânico). Esses aditivos foram utilizados em substituição aos componentes tradicionalmente utilizados na indústria da borracha, visando reduzir a quantidade de zinco na formulação e a utilização de um óleo proveniente de fonte vegetal como plastificante/lubrificante. Iniciou-se o estudo com a caracterização química e térmica de cada aditivo alternativo a partir da análise termogravimétrica (TGA), espectrometria no infravermelho com transformada de Fourier (FTIR) e espectrometria de absorção atômica (AAS). Foram preparadas 15 misturas, sendo uma formulação padrão típica para banda de rodagem, e as demais variando-se o teor de óleo vegetal (3, 4, 6 e 8 phr), Zn orgânico (2, 3, 4 e 5 phr) e os dois aditivos juntamente (2 e 3 phr de Zn orgânico com 3 phr de óleo vegetal). Foram também preparadas formulações com ZnO com o teor de Zn equivalente às formulações propostas com os aditivos alternativos. A caracterização das composições foi realizada através de propriedades reométricas, calorimetria exploratória diferencial (DSC), densidade de ligações cruzadas, analisador de processamento da borracha (RPA), análise térmica dinâmico-mecânica (DMA), difração de raio X, envelhecimento acelerado em estufa e as propriedades físico-mecânicas de densidade, dureza, resistência à tração, resistência ao rasgamento, desgaste por abrasão e deformação permanente por compressão. Todos os resultados foram comparados à formulação padrão para bandas de rodagem. As características térmicas e químicas sugeriram que o óleo proveniente de fonte vegetal apresenta uma estrutura típica de um éster aromático derivado do óleo de soja e o Zn orgânico apresenta estrutura típica de um carboxilato de zinco aromático. A análise de DSC confirmou o efeito lubrificante do óleo proveniente de fonte vegetal, visto que não houve redução da temperatura de transição vítrea dos compostos. As propriedades físico-mecânicas e o envelhecimento acelerado em estufa indicam que o melhor desempenho foi alcançado com 3 phr de Zn orgânico e 3 phr de óleo proveniente de fonte vegetal, ocasionando assim em uma redução de 50% do teor de óleo plastificante e de 75% do teor de zinco, sem afetar adversamente as propriedades do artefato final.
Keywords: Borracha - Aditivos; Química da borracha; Automóveis - Pneus